2014
DOI: 10.1080/19440049.2014.926399
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of trichothecenes in breadsticks by gas chromatography-triple quadrupole tandem mass spectrometry

Abstract: Breadsticks are pencil-sized sticks of dry bread widely consumed as a pre-meal appetiser. They are basically wheat-based snacks, which makes them a good matrix to evaluate mycotoxin contamination, since wheat is very susceptible to fungal attack. In this sense, the fast, selective and sensitive gas chromatography-triple quadrupole tandem mass spectrometry (GCQqQ-MS/MS) method proposed here allows simultaneous determination of deoxynivalenol (DON), 3-acetyldeoxynivalenol, fusarenon-X, diacetoxyscirpenol, nivale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…In general, C 18 and PSA are, again, the sorbents most commonly applied in d-SPE, but the combination of these two with Al-N also showed good results [70]. C 18 has been used alone for the extraction of cereals [68,69,73,76], while PSA has been used without C 18 for the extraction of dairy products [67], bee-pollen-based food supplements [71] or cereals [67,70,71,74]. As an example, Fig.…”
Section: Mycotoxin Analysismentioning
confidence: 95%
See 3 more Smart Citations
“…In general, C 18 and PSA are, again, the sorbents most commonly applied in d-SPE, but the combination of these two with Al-N also showed good results [70]. C 18 has been used alone for the extraction of cereals [68,69,73,76], while PSA has been used without C 18 for the extraction of dairy products [67], bee-pollen-based food supplements [71] or cereals [67,70,71,74]. As an example, Fig.…”
Section: Mycotoxin Analysismentioning
confidence: 95%
“…Rodríguez-Carrasco et al [68] carried out a comparison between MSPD and QuEChERS for the extraction of eight trichotecene mycotoxins from wheat-based breadstick snacks followed by GC-MS/MS analysis. They found that QuEChERS extraction is faster and less laborious, and shows better extraction efficiencies (recoveries higher than 80% in most cases) than MSPD (recoveries of 46-89%).…”
Section: Mycotoxin Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…LC-MS methods were developed for determination of several mycotoxins from food microbes [49 ,50,51]. GC-MS approach is another important tool for foodomics [52][53][54]. CE-MS has been established as a versatile and robust tool providing fast, efficient and automated analytical separation techniques used for food analysis.…”
Section: Metabolomics In Food Microbiologymentioning
confidence: 99%